2021
DOI: 10.31703/grr.2021(vi-iii).03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Government Programs & Policies to Eradicate Gender Disparities in Pakistan

Abstract: Like many other developing nations, Pakistan is also facing a gender gap in its socio-cultural spheres. Since independence, many programs and policies have been made in public and private sector domains to eradicate these gender disparities. This paper aims to evaluate these programs and policies by encountering their salient features and how far these programs and policies proved to be fruitful in bridging this gap. The evaluation is done majorly through a desk review of the secondary data drawn from reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was also found in the literature that less number of female child was unvaccinated in FATA as compared to male child [ 55 ]. It may also be due to the impact of programs, Government of Pakistan has started like the KPCSW program and gender program to empower women of West Pakistan [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found in the literature that less number of female child was unvaccinated in FATA as compared to male child [ 55 ]. It may also be due to the impact of programs, Government of Pakistan has started like the KPCSW program and gender program to empower women of West Pakistan [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the respondents (84.4%) of this study were male, and the Chi-square test results imply that they were the main actors choosing the residential locations for their families. This reflects the dominantly patriarchal character of Pakistani society, where male heads of the households make the key decisions [53]. A study found gender to be a significant factor of residential location choices in Alexandria, Egypt [29].…”
Section: Discussionmentioning
confidence: 99%
“…After the 2018 General Elections in Pakistan, the government devised more specific and inclusive plans to implement the RTE for children, adults, and youth to ensure gender equality. However, gender equality and the realization of SDGs without involving faculty members will not yield the desired outcomes(Nawaz et al, 2021). Most people today believe that faculty members are essential to enhancing the quality of Education and that the only factor limiting the quality of an education system is the calibre of its faculty members.…”
mentioning
confidence: 99%